COVID-19 treatment during and after recovery: What to expect - Ari Fahrial Syam (World Nutrition Journal, 2020)
Currently, there are no clinically specific drug for COVID-19, neither novel treatments nor vaccines. Hospitals and researchers over the world are testing many different therapies on coronavirus-positive patients in an effort to find a potential COVID-19 treatment, a few medications that have been making a buzz in the science community such as remdesivir, hydroxychloroquine and chloroquine, favipiravir, oseltamifir, lopinavir/ritonavir, azithromycin, plasma convalescent, dexamethasone and stem cell.